The visual distortion in the streets, and its reflection on the mental image of the city (Case study: Tripoli Street in the city of Misurata) (Journal of Technology Research, 2025)
This study aims to explore the impact of visual distortions on the mental image of the city through a case study of Tripoli Street in the city of Misrata. The research relied primarily on a questionnaire to collect data from local residents, in addition to reviewing specialized literature addressing aspects of visual distortion and its effects on the urban environment. Data were analyzed statistically and interpreted objectively. The findings revealed a range of visual distortions, including deteriorated building façades, random proliferation of advertising signs, poor maintenance of sidewalks and lighting, and a lack of harmony in architectural and design elements. These factors contributed to visual distraction and the loss of the street’s and the city’s visual identity. The results also indicated that such distortions negatively affect the overall aesthetic of the city and the psychological and social well-being of its residents, who expressed feelings of discomfort and detachment due to the absence of unified visual coordination. The study recommends implementing plans to reorganize and unify building façades, enhance urban environmental elements through strict regulatory policies, and develop projects to rehabilitate the visual landscape. Emphasis should be placed on reinforcing the city’s cultural and aesthetic identity to promote a positive mental image and boost its social and tourism appeal.
Keywords: Visual distortion; pathways; mental image; Tripoli Street; mental perception